Processing instruction: Learning complex grammar and writing accuracy through structured input activities - Modirkhamene, Sima; Pouyan, Aram; Alavinia, Parviz (Universitas Pendidikan Indonesia, 2018)
Aimed to change the way input is perceived and processed, processing instruction (PI) tends to help learners focus on particular grammatical forms and alter their inappropriate processing problems so that they make a better form-meaning connection. As an attempt to extend the existing research on the use of PI, the present study was carried out to examine 40 elementary EFL learners’ grammatical achievement having been exposed to PI-based structured input activities. Two groups of learners, namely, PI (n = 20) and traditional instruction (TI, n= 20) were instructed the simple past tense –ed using PI-guided structured input activities and the conventional deductive method, respectively. Findings obtained from a set of interpretation and production tasks in pre- and post-test stages (immediate and delayed) revealed the superiority of the PI group both in the short term and the long run when compared to their peers instructed through the conventional deductive approach. Furthermore, within-group comparisons revealed some variation in participants’ performance in interpretation vs. production tasks. The discrepant findings in the production against interpretation tasks were also confirmed by what we obtained from the attitude survey; indicating that although the learners appreciated the effective role of PI in their results of attitude survey, confirming learners’ appreciation of the effective role of PI in their comprehension of the target structure, they were not very positive to the production tasks. It is concluded that different stages of comprehension and production in second language development, reflected as the general proficiency of the learners, potentially differ in terms of drawing learners’ attention to target structures more specifically when the tasks (e.g., production) are more cognitively demanding.